1.5 °C degrowth scenarios suggest the need for new mitigation pathways - Lorenz T. Keyßer (Nature Portfolio, 2021)
Established climate mitigation modelling relies on controversial negative emissions and unprecedented technological change, but neglects to consider degrowth scenarios. Here the authors show that degrowth scenarios minimize many key risks for feasibility and sustainability and thus need to be thoroughly assessed.